An Expedited Diagnostic Algorithm for Lumbosacral Pain: "The Best Likelihood Scenario Approach". Issue 12 (14th July 2015) - Stojanovic, Milan P.; Engel, Andrew J.
Abstract: Introduction: The logic behind diagnostic blocks is very straightforward. What has not been determined is the way diagnostic blocks can be best used. Study Design: Philosophical essay. Discussion: The interventional pain management physician would serve as the diagnostic expert by efficiently determining the source of the patient's pain. Conclusion: "The Best Likelihood Scenario" might improve diagnostic accuracy while decreasing societal costs.